A method to decipher the time distribution in astronomically forced sedimentary couplets. (August 2020) - Ma, Chao; Meyers, Stephen R.; Hinnov, Linda A.; Eldrett, James S.; Bergman, Steven C.; Minisini, Daniel
Abstract: Sedimentary couplets that are generated by astronomical forcing are common in pelagic and hemipelagic depositional settings. This study disentangles the time scales (sedimentation rates) of the two lithofacies that contribute to such astronomically-forced couplets, by introducing the Alpha method. This new method can be applied to precession or obliquity-forced sedimentary records, and compares the frequency modulation of an astronomical cycle model with the thicknesses of the couplets. The method is demonstrated on a synthetic model of a precession index-forced succession of limestone-marlstone couplets. Finally, the methods is applied to two case studies: for the Middle Cenomanian Eagle Ford Formation (Iona-1 core, Texas), sedimentation rates are estimated as 0.85–1.02 cm/kyr for the marlstone and 4.70–5.65 cm/kyr for the limestone; for the Middle Eocene IODP Expedition 342 Site U1408, sedimentation rates are 1.70–1.84 cm/kyr for the white nannofossil ooze and 2.54–2.75 cm/kyr for the greenish nannofossil-rich clay. More generally, studies of paleoclimate and geochemical evolution at the sub-Milankovitch scale can benefit from this method. Highlights: The "Alpha method" is developed to estimate facies-related sedimentation rates in astronomical forced strata with two alternating facies. The "Alpha method" is demonstrated to be robust on simulated data. The "Alpha method" is applied to the Mid-Cenomanian Event in the Iona-1 core and the Middle Eocene IODP Site U1408 core. The first case indicates sedimentation rates of 0.85–1.02 cm/kyr and 4.70–5.65 cm/kyr for the two facies. The second case reveals sedimentation rates of 1.70–1.84 cm/kyr and 2.54–2.75 cm/kyr for the two facies.